Cooperation between SSTC NRS and the EU in the Area of Nuclear Safety - Pauwels, H.; Daures, P.; Stockmann, Y.J.; Vegh, J. (Ядерна та радіаційна безпека, 2016)
The paper first briefly outlines the main characteristics of the EU assistance programs aimed to enhance nuclear safety in the Beneficiary countries. Then EU assistance provided to the Ukrainian regulator (SNRIU) is detailed, with specific emphasis on projects enhancing the capabilities of SSTC NRS as technical support organisation (TSO) to SNRIU, including training and tutoring (T&T) activities. The changing role of SSTC NRS in the cooperation activities is described as well. The broad range of cooperation is then illustrated by some selected projects focusing on various technical areas (e.g. severe accident management and mitigation, radioactive waste and spent fuel management, NPP service time extension, plant performance monitoring and operating experience feedback). Finally, the paper briefly discusses the future perspectives of the nuclear safety cooperation between the EU and Ukraine На початку статті коротко викладені основні характеристики програм підтримки ЄС, спрямованих на підвищення ядерної безпеки в країнах-бенефіціарах. Далі детально описується підтримка ЄС, що надається українському регулюючому органу (ДІЯРУ) з акцентом на проекти, спрямовані на розширення можливостей ДНТЦ ЯРБ як організації технічної підтримки (ОТП) ДІЯРУ, охоплюючи навчання і наставництво. Описується зміна ролі ДНТЦ ЯРБ у заходах зі співробітництва, широкий спектр співпраці в рамках деяких вибраних проектів з акцентом на різні технічні області (наприклад, управління важкими аваріями і пом’якшення наслідків, поводження з радіоактивними відходами та відпрацьованим паливом, продовження терміну експлуатації АЕС, контроль робочих характеристик станції та обмін досвідом експлуатації). Стисло обговорюються майбутні перспективи співпраці ЄС та України у сфері ядерної безпеки. В начале статьи кратко изложены основные характеристики программ поддержки ЕС, направленных на повышение ядерной безопасности в странах-бенефициарах. Далее подробно описывается поддержка ЕС, предоставляется украинском регулирующему органу (ГИЯРУ) с акцентом на проекты, направленные на расширение возможностей ГНТЦ ЯРБ как организации технической поддержки (ОТП) ГИЯРУ, включая обучение и наставничество. Описывается изменение роли ГНТЦ ЯРБ в мероприятиях по сотрудничеству, широкий спектр сотрудничества в рамках некоторых выбранных проектов с акцентом на различные технические области (например, управление тяжелыми авариями и смягчения последствий, обращение с радиоактивными отходами и отработанным топливом, продление срока эксплуатации АЭС, контроль рабочих характеристик станции и обмен опытом эксплуатации). Кратко обсуждаются будущие перспективы сотрудничества ЕС и Украины в сфере ядерной безопасности.